Automatic recognition of type of FEC codes in a robust environment - Khng, Qian Yu (2016)
Forward error correcting (FEC) channel codes play a vital role in improving the reliability of digital transmissions. In practice, accurate information about the type of FEC codes and code parameters used for encoding must be known at the receiver end. However, in an espionage and counter-espionage context where there is a need for communication intelligence, the code types and code parameters are unknown, and blind recognition of the same is mandatory for efficiency in cracking the encryption. This paper describes a methodology for classifying FEC codes without a priori knowledge of the coding scheme or code parameters, in both erroneous and non-erroneous environments. Different classes of FEC codes exhibit unique characteristics due to their structural differences, thus novel methodologies were specifically developed for use in a classification framework to pick up on these features variances. Analyses of these features will allow an uninformed observer to reverse-engineer the encoder structure and subsequently decode the data.